CHARACTERISTIC OF PARENTS’S ACCEPTANCE IN GETTING CHILD DIAGNOSIS AS AUTISM - Rahma Furi Sagita; Ahmad Suryawan; Wahyul Anis (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground: Autism is a child development disorder which usually late in case finding and intervention. It used to done in 30 month old of child. In Dr. Saiful Anwar Malang Regional Hospital, it was found that the average of case finding in 48 month of child. This study aims to determine how the acceptance of parents while getting diagnosis of their child and their action to give their child autism intervention. Method: This study used a qualitative research design with a phenomenological approach. Data colleted by in-depth interviews with 6 informants. Data analysis used Collaizi's (1978) Nine Steps method. Results: Most informants were late in recognizing the symptoms of autism in children, but they had a positive perception of the received diagnosis. All informants have felt bad feelings due to the diagnosis received, but have had coping methods for these feelings and have given autism interventions to children. Factors that influence parental acceptance include the level of education, knowledge, age, occupation, household harmony, social support, economic conditions, ethnicity, interaction between informants and experts, the clarity of symptoms shown by the child and the presence of siblings. Conclusion: Parental acceptance is a process from refusing, getting angry, bargaining, to accepting. In the process of being accepted, parents continue to make efforts to save children